Wireless networks : from the physical layer to communication, computing, sensing, and control - Franceschetti, Giorgio; Stornelli, Sabatino (Academic Press, 2006)
Awarded by the International Calabria's Prize!This multidisciplinary volume originates from lectures presented at a short course on wireless communications in Capri, Italy. This globally attended conference has produced an exceptional book written by pioneers in the field. Lecturers at Capri included pillars in the fields of electromagnetics, communications, information technology and mathematics. As communications technology becomes increasingly wireless, an interdisciplinary viewpoint is necessary for professionals to correct problems and avoid others before they occur.<br.